Pendekatan Contextual Teaching And Learning (Ctl)Sebagai Upaya Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Matematika Pecahan Sederhana Di Kelas Iii Mi Maarif Sendang Kulon Progo - Laelatul Badriah (Universitas Alma Ata, 2014)
The background of this research is the low of student’s mathematic achievement especially on simple matter fractions third grade students at MI Maarif Sendang Kulon Progo. The Learning process is abstract. The Students don’t find the meaning of the subject matter so that it affects a perception that mathematics is difficult. One of the efforts to improve students' mathematics achievement is by applying a contextual approach. Optimally subject matter associated with real life so that students understand the learning concepts presented by teachers and find the meaning of the subject matter which is studied. The implementation of the actions is performed by two cycles of the three meetings for each cycle collaboratively. Data was collected through observation, tests, interviews, documentation, and field notes. Data analysis was done by using qualitative descriptive analysis, by giving meaning to the data which is collected and draw conclusions from that meaning. The assessment of the validity of the data is done by using the technique of triangulation of data. The results showed that learning mathematics can be said to be a simple matter fractions through contextual approach because it reflects the 7 principles of CTL and contextual learning mathematics through an approach can increase student’s achievement than class average of 67.00 increased to 78.33 .